PERAN LEMBAGA WILAYATUL HISBAH DALAM SISTEM PEREKONOMIAN ISLAM - abdul Hamid (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
To control / supervise the implementation of Islamic Shari'at in the field the Regional Government establishes a Wilayatul Hisbah (WH) body whose work procedures and authorities are regulated in the Decree of the Governor of Nanggroe Aceh Darussalam Number 01 of 2004. In applying certain aspects of sharia law. Therefore, improving the quality of human resources through the Islamic structural values approach is considered by many to be the right step, because it can control deviations and is also in accordance with the cultural values of the Acehnese people, which have historically been known with three features, namely, education , religion and customs.